Exhibiting the Past Public Histories of Education - Herman, Frederik; Braster, Sjaak; del Mar del Pozo Andrés, María (Public History in European Perspectives, 2022)
With respect to public issues, history matters. With the worldwide interest for historical issues related with gender, religion, race, nation, and identity, public history is becoming the strongest branch of academic history. This volume brings together the contributions from historians of education about their engagement with public history, ranging from musealisation and alternative ways of exhibiting to new ways of storytelling.